The Effectiveness of Worded Pictures in Teaching Descriptive Writing to Eight Grade Students of SMPN 2 Amarasi Selatan Satap - Serang, Yenny Jahra (Journal of Language, Education, Literature, and Culture, 2025)
The objective of the research is to know whether using worded pictures is effective in teaching descriptive writing to eighth-grade students of SMPN 2 Amarasi Selatan SATAP. The research was carried out at SMPN 2 Amarasi Selatan SATAP. The participants of this study were eighth-grade students in the school year 2013/2014. It applied a quasi-experimental design using a single-group approach, involving one class consisting of 39 students. The students were taught by using worded pictures for four meetings. Following the intervention, data were collected through a test and subsequently analyzed using a t-test. Based on the result of data analysis, the findings indicated that the use of worded pictures is effective in enhancing descriptive writing skills among the eighth-grade students of SMPN 2 Amarasi Selatan SATAP in the school year 2013/2014. The mean score on the pre-test was 1.87, which falls within the ‘very poor’ category. In contrast, the post test mean score increased to 3.33, classified as ‘average.’ This improvement indicates a substantial gain in students’ writing performance, with a percentage increase of 78.07%. Furthermore, the t-test analysis revealed that the obtained t-value (-21.43) exceeds the critical t-value (2.024). Therefore, the alternative hypothesis - stating that teaching descriptive writing using worded pictures is effective – was accepted. These findings suggest that teachers should consider incorporating worded pictures as a pedagogical strategy for teaching descriptive writing, as such visual aids can assist students in organizing and expressing their ideas